2016
DOI: 10.1177/1359105316639435
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of appearance and health messages present in pregnancy magazines

Abstract: This study explored appearance-related images and messages present in pregnancy magazines (e.g. Fit Pregnancy, Pregnancy & Newborn, and Pregnancy Magazine). A substantial portion of advertisements and articles promoted appearance-related products or products for postpartum weight loss. Health messages and messages related to diet and exercise were also present. Images also sexualized pregnant women's bodies. Appearance-related messages aimed toward pregnant women may be problematic and may contribute to body d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…While tobacco advertising, including celebrity endorsements, is banned or strictly regulated in the United States and many other countries, there are no FDA restrictions on SNS-based e-cigarette brand pages as of 2016 (FDA, 2016). In previous research, celebrity endorsers act as role models whom fans look to for social and behavioural cues (Boepple and Thompson, 2016; Tatangelo and Ricciardelli, 2015). We hypothesized that an e-cigarette SNS brand page with celebrity endorsers would more strongly impact attitudes towards e-cigarettes and smoking intentions, compared to non-celebrity endorsers or products only.…”
Section: Introductionmentioning
confidence: 99%
“…While tobacco advertising, including celebrity endorsements, is banned or strictly regulated in the United States and many other countries, there are no FDA restrictions on SNS-based e-cigarette brand pages as of 2016 (FDA, 2016). In previous research, celebrity endorsers act as role models whom fans look to for social and behavioural cues (Boepple and Thompson, 2016; Tatangelo and Ricciardelli, 2015). We hypothesized that an e-cigarette SNS brand page with celebrity endorsers would more strongly impact attitudes towards e-cigarettes and smoking intentions, compared to non-celebrity endorsers or products only.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies investigated the effect of magazines primarily dedicated to pregnant women [ 160 162 ]. The main topics were dieting, weight loss, and physical exercise.…”
Section: Resultsmentioning
confidence: 99%
“…Also, a study exploring appearance-related images and messages in pregnancy magazines found that a substantial portion of advertisements promoted products for postpartum weight loss. The research concluded that these magazines may contribute to body dissatisfaction [ 19 ]. A recent systematic review found that the focus for investigation on DRA had been on associations with physical challenges such as pelvic floor dysfunction, low back and pelvic girdle pain, and there were few studies on associations with body image, physical appearance and body satisfaction [ 20 ].…”
Section: Introductionmentioning
confidence: 99%